Lifestyles concepts and ecological behavior: an empirical study in India - Ahmad, Asad; Adnan, Arham; Khan, Mohammed Naved (Serbian Journal of Management, 2019)
The constant issues related to the environment degradation faced by the world are thought to be reflected in the buying and consumption behavior of the consumers. The study of green consumer behavior is one of the vital present-day researches. The purpose of the present study is to explore the lifestyles of Indian consumers and their influence on the ecologically conscious behavior. For this purpose the researchers have employed the lifestyle scale along with the actual commitment subscale. The study results are based on researcher controlled student sample of 150 respondents. The data was analyzed using tools like SPSS 20.0 and AMOS 20.0. The results suggest that аchievers and аdventuresome are significant predictors of the ecological conscious behavior.
Keywords: CONSUMERS; ECOLOGY; Conscious Will; behavior; lifestyle